EVALUASI MANAJEMEN PENYIMPANAN OBAT DI GUDANG OBAT INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH dr. R. SOEDJONO SELONG LOMBOK TIMUR - Nurul Qiyaam; Nur Furqoni; Hariati (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
The storage management of drugs in hospitals must be good and true that the availability of pharmaceuticals is guaranteed in accordance with the needs of the hospital. This study aims to determine whether the drug storage in warehouses medicine is good and right and knowing how storage management of drugs in pharmaceutical warehouse Pharmacy Installation District General Hospital dr. R. Soedjono Selong. This is description research. Data collection using observational methods tailored to the interview with the standard parameter storage management medicine is good and right. The results showed that storage of medicines in pharmaceutical warehouse Pharmacy Installation District General Hospital dr.R.Soedjono Selong already well and truly based on five indicators of drug management at the stage of distribution, namely: the accuracy of data on the number of drugs on the card stock, the system arrangement of the warehouse, the percentage the value of the drug expired or damaged, the percentage of stock die and availability of drugs, as well as standards-based storage value of drugs that have three categories: category management stock classified as "good" with a value of 14, the category stock control classified as "good" with a value of 16 and category storage conditions classified as "good" with a value of 16.